A geometrical view for multiple gross errors detection, identification, and correction in power system state estimation - Bretas, Newton G.; Piereti, Saulo A.; Bretas, Arturo S.; Martins, Andre C. P. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
In this paper a geometrical approach is described to detect, identify, and recover multiple gross errors in power system state estimation. Using the classical WLS estimator, the measurement residuals is computed, and then the error is composed. For the detection and identification of the measurements with gross errors, the composed measurement error in the normalized form (CME N) is used. The measurement magnitude corrections otherwise are performed using the composed normalized measurement error (CNE). To give support to the detection and identification of the measurements containing gross errors, a generalization of the classical largest normalized residual test is provided. © 1969-2012 IEEE.
Keywords: Composing errors; gross errors analysis; orthogonal projections; recovering errors; state estimation